Distribution of CD8 and CD20 lymphocytes in chronic periapical inflammatory lesions - Philippi,Christine Kalvelage (2003)
The objective of this study was to investigate the distribution of CD8+ and CD20+ lymphocytes in chronic periapical inflammatory lesions. A total of 90 periapical inflammatory lesions (chronic abscesses, abscessed cysts, and inflammatory cysts) were evaluated. The biotin-streptavidin immunohistochemical technique was used to identify cytotoxic/suppressor T-lymphocytes (CD8) and B-lymphocytes (CD20). Age ranged from 10 to 67 years. Patients between 26 and 45 years old (54.4%), females (52.2%), and white patients (74.4%) were more frequently affected. CD8+ cell distribution was as follows: 1) fibrous capsule: diffuse in 58.8% of chronic abscesses and absent in 64.1% of abscessed cysts and in 70.6% of inflammatory cysts; 2) infiltration zone: diffuse in 100% of abscessed cysts and in 82.4% of inflammatory cysts; 3) sub-epithelial zone: absent in 53.0% of inflammatory cysts and diffuse in 56.4% of abscessed cysts; 4) suppurative zone: diffuse in 100% of chronic abscesses and in 97.5% of abscessed cysts. CD20+ cell distribution was as follows: 1) fibrous capsule: absent in 100% of inflammatory cysts, in 94.8% of abscessed cysts, and in 88.3% of chronic abscesses; 2) infiltration zone: diffuse in 100% of abscessed cysts and in 53% of inflammatory cysts; 3) sub-epithelial zone: absent in 58.8% of inflammatory cysts and focal in 46.2% of abscessed cysts; 4) suppurative zone: diffuse in 100% of abscessed cysts and in 100% of chronic abscesses. The distribution of the lymphocytic infiltrate in the lesions was usually diffuse for both types of lymphocytes.